SOSIALISASI ART THERAPY SEBAGAI MEDIA KOMUNIKASI ANAK - Kusuma Wardani, Yulia; Mahasiswa KKN Universitas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Student community service through the Community Service Program (KKN) is a tangible contribution from students in understanding community life and its problems. Art therapy is a psychological approach that utilizes artistic expression as a medium for communication and self-exploration, particularly effective for children who have difficulty expressing emotions verbally. This outreach activity aims to introduce the concept of art therapy to elementary school students as a safe, creative, and therapeutic communication alternative. The target participants are focused on 4th and 5th grade students at SDN Jagabaya I, Way Halim District, taking into account the cognitive and emotional development of children aged 9–11 years who are in the concrete operational stage according to Piaget's theory. At this stage, children begin to be able to understand visual symbols, think logically, and demonstrate emotional readiness to manage more complex social dynamics. The implementation method includes an explanation of the concept of art therapy, a drawing session on the theme "Me and My Feelings," and a reflective discussion of the resulting work. Observations show that this approach is able to increase active participation, self-expression, and social interaction among students. Art therapy has proven to be an inclusive and effective communication medium in supporting the psychosocial development of elementary school-aged children. This activity also opens up space for teachers and parents to understand the importance of non-verbal communication in the process of child growth and development.